The role of virtual influencers in shaping fashion preferences among Malaysian generation alpha: perceptions, engagement and consumer trust - Hassan, Normaziana; Jamaludin, Juaini; Shawalludin, Syahrini; Hasan, Asrol (Universiti Teknologi MARA, Kedah, 2025)
Virtual influencers have emerged as a powerful force in digital marketing, particularly within the fashion industry. Unlike traditional influencers, these AI-generated personalities engage with audiences through immersive content, shaping trends and consumer preferences. This study examines the role of virtual influencers in influencing fashion choices among Malaysian Generation Alpha, focusing on perceptions, engagement patterns, and consumer trust. Using a quantitative approach, a structured online survey was conducted among 400–500 respondents aged 10–14 years. The findings reveal that Generation Alpha exhibits high engagement with virtual influencers, particularly on platforms like TikTok and Instagram, where interactive content fosters deeper connections. Trust in virtual influencers significantly influences purchase intent, with respondents perceiving them as reliable fashion trendsetters. Additionally, economic and cultural factors shape how young consumers interact with these digital personas, as parental guidance and affordability remain key considerations. Multiple regression analysis and structural equation modeling (SEM) confirm that trust and engagement mediate fashion purchasing behavior. These insights provide actionable strategies for brands looking to leverage virtual influencers in digital marketing campaigns targeting young consumers. The study highlights the growing authenticity paradox of virtual influencers, where AI-generated personas can build stronger consumer trust than traditional human influencers. Future research should explore the long-term impact of virtual influencers on brand loyalty and consumer identity formation.